2019
DOI: 10.1088/1361-6641/ab0efc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of uniaxial strain on the performance of armchair graphene nanoribbon resonant tunneling diode

Abstract: Electronic performance of armchair graphene nanoribbon (AGNR) resonant tunneling diodes (RTDs) is influenced by strain effects, when they are mounted on the stretchable substrates or mechanically deformed due to real working conditions. Therefore, it is important to investigate how uniaxial strain can impact the performance of AGNR RTDs. In this paper, two platforms of AGNR RTD namely width-modified AGNR RTD and field-modified AGNR RTD are introduced and they are under both compressive and tensile uniaxial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For example, the undoped GNR RTD exhibits high PVR ( 10 4 ) by just introducing quantum dots into the nanoribbon [47]. Pristine AGNR based RTD also shows improved performance through local strain in the channel and barrier regions [27]. AGNR based field effect transistors embedded with nanopores exhibits improved I p and PVR with lower well width and drain voltage respectively [48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the undoped GNR RTD exhibits high PVR ( 10 4 ) by just introducing quantum dots into the nanoribbon [47]. Pristine AGNR based RTD also shows improved performance through local strain in the channel and barrier regions [27]. AGNR based field effect transistors embedded with nanopores exhibits improved I p and PVR with lower well width and drain voltage respectively [48].…”
Section: Resultsmentioning
confidence: 99%
“…Here, the current flow does not suffer from low carrier mobility and charge storage effects, thereby giving rise to extremely fast operating devices with abrupt turn-on and turn-off facilities. Recently, the study of NDR in graphene has drawn potential research interest due to the feasibility of making a quantum well (QW) structure out of a single graphene sheet through structural modifications [26][27][28][29]. Double barrier quantum well (DBQW) structures have been realized by adjusting the width of armchair graphene nanoribbon (AGNR) to obtain NDR.…”
Section: Introductionmentioning
confidence: 99%
“…For an applied voltage, the quasi-quantized states shift to lower energy and, when the Fermi level of the source becomes aligned with the quasi-quantized states, the maximum current, I peak , occurs. In the high bias, when the quantized level goes below the Fermi [46] Graphene/h-BN heterostructure 3.9 Zoghi and Goharrizi [20] Strain-induced (ε = 5%) 5.63 Zoghi and Kabir [47] Width-modified 15-AGNR RTD (0% strain) 3.49 Field-modified 15-AGNR RTD (0% strain) 17.83 Goharrizi et al [48] Antidote 3.31 Doping 1.09 Antidote/doping 9.46 energy, the current starts decreasing and it contributes to the valley current (I valley ).…”
Section: Single Barrier Systemmentioning
confidence: 99%
“…Moreover, the application of uniaxial strain has been proposed in order to achieve negative differential resistance (NDR) in graphene tunnel FETs [22] as well as in AGNR-based devices [23]. It has also been shown that the characteristics of AGNR resonant tunneling diodes are significantly influenced by uniaxial strain [24,25].…”
Section: Introductionmentioning
confidence: 99%